Fast mode decision algorithm - Maarif, Haris Al Qodri; Gunawan, Teddy Surya; Khalifa, Othman Omran (IIUM Press, 2011)
Fast mode decision is the developed algorithm intended for selectively choosing the mode decision used by the encoder. The default is the scalable video coding model \vhich is represented by Joint Scalable Video Model (JSVM). It has many mode decisions which are involved during the encoding process. The mode decisions are applied for motion prediction, either intra or inter prediction. Mode decisions in scalable video coding are the features which are available in previous video coding standard and some added features which are in line \vith scalability